2020
DOI: 10.1074/jbc.ra120.012792
|View full text |Cite
|
Sign up to set email alerts
|

Bile acid composition regulates the manganese transporter Slc30a10 in intestine

Abstract: Bile acids (BAs) comprise heterogenous amphipathic cholesterol-derived molecules that carry out physicochemical and signaling functions. A major site of BA action is the terminal ileum, where enterocytes actively reuptake BAs and express high levels of BA-sensitive nuclear receptors. BA pool size and composition are affected by changes in metabolic health, and vice versa. One of several factors that differentiate BAs is the presence of a hydroxyl group on C12 of the steroid ring. 12α-hydroxylated BAs (12HBAs) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 87 publications
(128 reference statements)
1
12
0
Order By: Relevance
“…How these transporters might modulate plasma levels of secondary BAs is not known and requires functional follow-up. Interestingly, Ahmad et al (2020) recently reported that the non-12a hydroxylated secondary species LCA induces the expression of the ileal manganese efflux transporter SLC30A10 via activation of VDR, which supports the existence of a functional link between BA and manganese metabolism. Additionally, we found four zincfinger-protein-related genetic variants (ZFN569, ZFN250, ZFN706, and JAZF1) to associate with five fecal BA entities, including fecal DCA and CDCA contents.…”
Section: Discussionmentioning
confidence: 81%
“…How these transporters might modulate plasma levels of secondary BAs is not known and requires functional follow-up. Interestingly, Ahmad et al (2020) recently reported that the non-12a hydroxylated secondary species LCA induces the expression of the ileal manganese efflux transporter SLC30A10 via activation of VDR, which supports the existence of a functional link between BA and manganese metabolism. Additionally, we found four zincfinger-protein-related genetic variants (ZFN569, ZFN250, ZFN706, and JAZF1) to associate with five fecal BA entities, including fecal DCA and CDCA contents.…”
Section: Discussionmentioning
confidence: 81%
“…However, IBABP expression, like FGF19, was robustly induced by H10 and, to a lesser extent, by H90. As the commercial formulation appeared to yield results more consistent with published findings [15], we favored it to perform the experiments in 2D-hIO below.…”
Section: Human Intestinal Organoidsmentioning
confidence: 76%
“…Unconjugated bile acid mixes were prepared and dissolved in DMSO according to proportions we have published previously [15]. H10 (i.e., 10% 12-HBA, 90% non-12-HBA) consists, on a molar basis, of: 7% cholic acid (CA), 3% deoxycholic acid (DCA), 86.85% chenodeoxycholic acid (CDCA), 2.25% ursodeoxycholic acid (UDCA), and 0.90% lithocholic acid (LCA).…”
Section: Bile Acid Mixesmentioning
confidence: 99%
See 1 more Smart Citation
“…The loss-of-function mutations of SLC30A10 are associated with adult-onset Parkinsonism. Expression of SLC30A10 and cellular Mn efflux are regulated by the composition of bile acids [ 67 ].…”
Section: Discussionmentioning
confidence: 99%